Pengaruh Profitabilitas, Ukuran Perusahaan dan Struktur Modal terhadap peringkat Obligasi pada Perusahaan Sektor Keuangan yang Terdaftar di Bursa Efek Indonesia Periode 2013 - 2016 - Noviarti (Fakultas Ekonomi dan Bisnis Universitas Satya Negara Indonesia, 2018)
The purpose of the study was to examine the effect of profitability, firm size and capital structure on bond rating. Sampling technique with purposive sampling. Number of samples from 8 financial sector companies with observation period over 4 years. The analysis technique used is ordinal logistic regression. The test results show that the profitability and size of the company have a negative and significant impact on the rating of bonds. And the capital structure has a negative and significant effect on the bond rating. And simultaneously profitability, firm size and capital structure affect the rating of bonds.